2018
DOI: 10.1101/254268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute antidepressant effect of ayahuasca in juvenile non-human primate model of depression

Abstract: 52The incidence of major depression in adolescents, aged between 15 to 18 years, reaches 53 approximately 14%. Usually, this disorder presents a recurrent way, without remission of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Some studies with animal models of depression, rodents and non-human primates, observed positive antidepressant effects with the use of ayahuasca or its specific components (81, 82, 83). Using the recently validated translational animal model of depression (84), young marmosets ( Callithrix jacchus ) were treated with nortriptyline during 7 days, a tricyclic antidepressant, or with a single dose of ayahuasca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies with animal models of depression, rodents and non-human primates, observed positive antidepressant effects with the use of ayahuasca or its specific components (81, 82, 83). Using the recently validated translational animal model of depression (84), young marmosets ( Callithrix jacchus ) were treated with nortriptyline during 7 days, a tricyclic antidepressant, or with a single dose of ayahuasca.…”
Section: Discussionmentioning
confidence: 99%
“…Using the recently validated translational animal model of depression (84), young marmosets ( Callithrix jacchus ) were treated with nortriptyline during 7 days, a tricyclic antidepressant, or with a single dose of ayahuasca. It was observed that ayahuasca increased fecal cortisol levels until 48 hours after it ingestion and presented more notable antidepressant effects than nortriptyline, since it reverted depressive-like behaviors and regulated cortisol levels faster and during more time (83). The modulation of HPA axis by antidepressants depend on the type of antidepressant used and the duration of treatment, acute or chronic.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that ayahuasca and its DMT and harmala alkaloids may provide therapeutic benefit for mental health conditions, including depression, anxiety, and substance abuse disorders ( Sarris et al, 2021 ; Uthaug et al, 2021 ; van Oorsouw et al, 2021 ; James et al, 2022 ). Placebo-controlled preclinical studies, as well as double-blind randomized placebo-controlled and observational naturalistic studies have reported antidepressant and anxiolytic effects ( Dos Santos et al, 2016 ; Cameron et al, 2018 ; Palhano-Fontes et al, 2018 ; Santos da Silva et al, 2018 ; Almeida et al, 2019 ; Sarris et al, 2021 ; Zeifman et al, 2021 ). Naturalistic ayahuasca studies have also reported increases in self-compassion, and self-assurance alongside mental health improvements ( Dominguez-Clave et al, 2021 ; Ruffell et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%